Antibacterial Activity of Mangrove Leaves Extract (Rhizopora Apiculata) Against Salmonella typhi Growth - Nurfadly, Nurfadly; Harahap, Sevani Ayu; Roslina, Ance; Sarirah, Munauwarus (Majalah Kedokteran Bandung, 2025)
Mangrove leaves (Rhizopora apiculata) contain antibacterial chemical compounds with antibacterial properties against various pathogens. Salmonella typhi, the causative agent of thyphoid fever, triggers a systemic infectious disease that can lead to complications and deaths if not treated properly.  This study aimed to screen the phytochemical content of R. apiculata leaf extract, evaluate its antibacterial activity against S. typhi, and determine the optimal inhibitory concentration. Leaves were collected from the Sicanang mangrove forest in Belawan, North Sumatra, Indonesia, and extracted using the maceration method with 96% ethanol.  Antibacterial effectiveness was assessed using disc diffusion method by measuring the zone of inhibition after exposure to mangrove leaf extract at concentrations of 40%, 60%, 80%, and 100%, with chloramphenicol as a positive control, to determine the most effective concentration for inhibiting the growth of Salmonella typhi. The results of the study showed that there were differences in inhibition zones in each group. Mangrove leaves extract at a concentration of 100% is the most effective in inhibiting the growth of Salmonella typhi compared to 80%, 60%, and 40% concentrations.